2012
DOI: 10.1037/h0094499
|View full text |Cite
|
Sign up to set email alerts
|

Work-ordered day as a catalyst of competitive employment success.

Abstract: Participants with more Work-Ordered Day program participation prior to employment had significantly longer average competitive employment duration even when controlling for prior work history. Participation in the Work-Ordered Day program is likely to improve work readiness. Further research is warranted to study which elements of the program may foment employment success. This could lead to increased implementation of the Work-Ordered Day program and its elements as precursors to employment for adults with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…Participation in work also helps to develop tangible skills, which improves work readiness and enhances capabilities to pursue life goals (Schonebaum & Boyd, ), which suggests likely activation of psychosocial mechanisms of self‐efficacy. This is consonant with Doyle et al () work that underscores self‐efficacy as an important mechanism by which clubhouses facilitate recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in work also helps to develop tangible skills, which improves work readiness and enhances capabilities to pursue life goals (Schonebaum & Boyd, ), which suggests likely activation of psychosocial mechanisms of self‐efficacy. This is consonant with Doyle et al () work that underscores self‐efficacy as an important mechanism by which clubhouses facilitate recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that participation in clubhouses can reduce likelihood of rehospitalization (Di Masso, Avi‐Itzhak, & Obler, ), enhance self‐reported recovery and perceived quality of life (e.g., Tsang, Ng, & Yip, ), improve employment outcomes (e.g., Schonebaum & Boyd, ), enhance general physical and mental health (e.g., Tratnack & Kane, ), and decrease utilisation of healthcare resources (Grinspan, ; Hwang, Woody, & Eaton, ). Clubhouse members also share a collective identity (Mandiberg & Edwards, ) and the social support at clubhouses is associated with greater understandings of recovery (Pernice‐Duca & Onaga, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the international literature on the effects of clubhouse membership and participation is limited. To date, studies have established initial evidence that clubhouses may contribute to assisting their members to get a job, stay in the job, and increase their wages (Schonebaum and Boyd, 2012; Schonebaum et al., 2006), but also that transitional employment appears to have limited effects with regard to assisting members in obtaining steady employment in competitive work (Pirttimaa and Saloviita, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, the number of clubhouses is increasing and their ideology and methods appear to fit well with the current policies, emphasizing engagement in meaningful occupations, independent living and social participation, rather than a narrow medical focus on remediation from illness and symptoms (14,15). Outcome-focused studies related to clubhouses have mostly been concerned with employment (16,17), and a review found that clubhouses were an effective means for supporting employment, reducing hospitalizations, improving quality of life, and increasing social integration and social competence (18).…”
Section: Introductionmentioning
confidence: 99%